2012
DOI: 10.1021/am201664n
|View full text |Cite
|
Sign up to set email alerts
|

Reduction and Functionalization of Graphene Oxide Sheets Using Biomimetic Dopamine Derivatives in One Step

Abstract: An easy and environmentally friendly chemical method for the simultaneous reduction and noncovalent functionalization of graphene oxide (GO) using dopamine derivatives is described. The reaction takes place at room temperature under ultrasonication of an aqueous suspension of GO and a dopamine derivative. X-ray photoelectron spectroscopy, FT-IR spectroscopy, and cyclic voltammetry characterizations revealed that the resulting material consists of graphene functionalized with the dopamine derivative. This one-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
109
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(115 citation statements)
references
References 46 publications
5
109
0
1
Order By: Relevance
“…Furthermore, for the GC sample, the appearance of a new C-N peak at the binding energy at about 285.8 eV strongly demonstrated the presence of the polydopamine coating in the multifunctional GC paper. 37,38,41 The above ESEM, XRD, UV-vis, FT-IR, and XPS observations proved that GO is indeed reduced by dopamine and polydopamine is present in the GC paper.…”
Section: This Journal Is ª the Royal Society Of Chemistry 2013mentioning
confidence: 68%
See 2 more Smart Citations
“…Furthermore, for the GC sample, the appearance of a new C-N peak at the binding energy at about 285.8 eV strongly demonstrated the presence of the polydopamine coating in the multifunctional GC paper. 37,38,41 The above ESEM, XRD, UV-vis, FT-IR, and XPS observations proved that GO is indeed reduced by dopamine and polydopamine is present in the GC paper.…”
Section: This Journal Is ª the Royal Society Of Chemistry 2013mentioning
confidence: 68%
“…5a): the C]O stretching vibration peak of carboxyl groups at 1729 cm À1 ; the aromatic C]C stretching vibration peak at 1621 cm À1 ; the O-H deformation vibration peak at 1395 cm À1 ; the C-OH stretching peak at 1220 cm À1 ; and the C-O stretching peak at 1049 cm À1 . [39][40][41] The disappearance of the typical C]O peak at 1729 cm À1 compared to original GO strongly demonstrated the reduction of GO to graphene by the reaction between carboxylic acid groups and amine groups (Fig. 5b).…”
Section: This Journal Is ª the Royal Society Of Chemistry 2013mentioning
confidence: 93%
See 1 more Smart Citation
“…Its high specific surface area makes it appealing as a support for synthesis of metal based catalysts. Graphenesupported catalysts have been reported in reactions such as biomimetric oxidation, photocatalytic, decomposition of hydrous hydrazine, hydrogen production from silicon photocathode and enhanced electro-catalytic oxidation of methanol [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [15] reported that the adhesive proteins secreted by mussels (PDA) can self-polymerize via a simple deposition process under alkaline conditions and attach the adhesive layer onto almost all types of surface, be it organic or inorganic. In the past years, a large amount of substrates have been functionalized with polydopamine, such as electrospun nanofibers [16][17][18] , clay [19][20][21] , carbon fiber [22] and graphene oxide [23][24][25] . As a non-covalent modification method, the PDA functionalization process has significant advantages, like high efficiency, ease of procedure, and mild reaction conditions, exclusive from concentrated acid and strong oxidation processes.…”
mentioning
confidence: 99%